The Effect of Hypnoteaching Learning Method on Students’ Problem-Solving Skills and Concept Understanding - Fitria Adelita; Achi Rinaldi; Fredi Ganda Putra (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
The purpose of this study is to know the impact of the method (hypnoteaching) on problem solving and conceptual comprehension of learners. This research represents the kind of research quasy experimental design. The sampling technique used is a random sampling cluster. The population in this study is the entire class vii MTS sa raudlatul huda al-islamy. The samples in this study are vii classes and vii class. the tools used are the test of problem solving and concept understanding. The multivariate analysis of variant (manova) with its degree of significance: 0.05, and concluding (1) is influenced by methods (hypnoteaching) on the faculty's problem-solving ability (2) there is the influence of the method (hypnoteaching) on the ability of discerning the learner's concept (3) on the influence of the method (hypnoteaching) on the problem solving and comprehension of learners.